A review: citrus species and application in plant cell culture - M. Fathil, Nur Alia; Mohamad Puad, Noor Illi (2015)
Citrus species is a well-known fruits that are consumed by people around the world which have made their production increasing and grown strongly since 1980s. The origin of this fruit is still unclear and controversial but hundreds kinds of citrus species have been divided them into two systems; Swingle and Tanaka. In particular country, only some species are being commercialized depending on the climate, disease problems and tradition. Citrus contains significant amount of vitamin C that is needed by human body as well as antioxidant and phytochemicals. Their nutritional properties for good health effect have given a great interest on the application of plant cell culture techniques such as callus cultures and cell suspension cultures that will overcome the problems in citrus plantation and production. There have been numerous reports on establishing citrus callus and cell suspension cultures for specific applications. Micropropagtion, somaclonal variations, somatic embryogenesis and haploid and dihaploid techniques are some of the important applications that are widely used to increase the genetic improvement of commercial citrus crop species. This review discusses on the citrus species and their cultivation, citrus main properties and mainly focusing on the applications and research development involving citrus cell cultures with the applications and study that have been done by the researchers.